Visualization of brain iron by mid-field MR. - Norfray, J F; Couch, J R; Elble, R J; Good, D C; Manyam, B V; Patrick, J L (American Journal of Neuroradiology, 1988)
Brain iron was visualized on a mid-field (0.5 T) scanner using a spin-echo pulse sequence. Methemoglobin was hyperintense on T1- and T2-weighted images. Deoxyhemoglobin, hemosiderin, and ferritin were seen as decreased intensity on T2-weighted images. The spin-echo pulse sequences were improved for identification of deoxyhemoglobin, hemosiderin, and ferritin by prolonging the TR to 3000 msec and the TE to 80-120 msec. Phase-encoding artifacts at the level of the sylvian fissures caused increased noise, obscuring the brain iron in the lentiform nuclei with the TE of 120 msec. This artifact was substantially reduced or eliminated by lowering the TE to 80 msec, changing the phase-encoding gradient to the Y axis, or using additional pulsing in the slice and read gradients. Use of either the improved spin-echo or gradient-echo pulse sequences on a mid-field MR scanner provides improved evaluation of brain iron.